Reliability Assessment of Interconnected Substations Using the Reliability Block Diagram Approach - Hermoyo, Ganis; Fitri, Ismi Rosyiana; Widyanto, Aji Nur (International Journal of Electrical, Computer, and Biomedical Engineering, 2025)
The reliability of substations plays a crucial role in maintaining the continuity and stability of power supply in transmission systems. This study evaluates the reliability level of two interconnected 150 kV substations using the Reliability Block Diagram (RBD) approach. The RBD model is applied to map the actual component configuration, from major component levels to the system level, based on operational age and component failure rate data. Simulation results show that System1 has a reliability value of 0.907735, while System2 reaches 0.979424. This discrepancy indicates a potential for reliability improvement through component rejuvenation strategies. A scenario simulating the replacement of critical equipment successfully increased the reliability of system1 to 0.980168 and raised the overall reliability of the interconnected system to 0.959989. These findings suggest that a prioritized maintenance or renewal of component strategy targeting critical component can significantly enhance the overall reliability of the transmission system.